The role of carbonyl reducing enzymes in oxcarbazepine in vitro metabolism in man - Malátková, Petra; Havlíková, Lucie; Wsól, Vladimír (Chemico-biological interactions, 2014)
Oxcarbazepine, a second generation antiepileptic drug belonging to the family of dibenz[b,f]azepines, is subjected to a rapid and extensive biotransformation. Oxcarbazepine demonstrates a low potential for drug interactions because its biotransformation is mainly mediated by the reduction pathway instead of oxidative pathways, which are very susceptible to drug interactions. The reductive metabolism of oxcarbazepine yields a 10-monohydroxy derivative (10,11-dihydro-10-hydroxy-carbazepine), which is responsible for the pharmacological activity. The identity and localization of enzymes participating in the reduction of oxcarbazepine in response to this active metabolite have remained unknown until now. Thus, we investigated the reductive metabolism of oxcarbazepine in human liver subcellular fractions and using recombinant carbonyl reducing enzymes. The reduction of oxcarbazepine was shown to occur largely in the liver cytosol rather than liver microsomes. Furthermore, the activity and stereospecificity of cytosolic carbonyl reducing enzymes toward oxcarbazepine were assessed. Of the eight tested enzymes, six reductases were identified to contribute to the reduction of oxcarbazepine. The highest activities were demonstrated by AKR1C1, AKR1C2, AKR1C3, and AKR1C4. The contribution of CBR1 and CBR3 to the reduction of oxcarbazepine was also significant, although their role in oxcarbazepine metabolism in vivo is unclear.
Keywords: Anticonvulsants; játra; Carbamazepine; jaterní mikrozomy; Chromatography, High Pressure Liquid; Short-chain dehydrogenase/reductase; Carbonyl reducing enzymes; Microsomes, Liver; Humans; Carbonyl reductase; antikonvulziva; cytosol; oxidace-redukce; alkoholoxidoreduktasy; Oxcarbazepine; lidé; Reductive drug metabolism; Cytosol; AKR; oxkarbazepin; Liver; Oxidation-Reduction; karbamazepin; Alcohol Oxidoreductases; vysokoúčinná kapalinová chromatografie